Work accidents and automatic circuit reclosers in the electricity sector: beyond the immediate causes - Nunes da Silva, Alessandro Jose (2018)
The Brazilian electricity sector has recorded high work-related mortality rates that have been associated with outsourcing, used to cut costs. In order to decrease the power outage time for consumers, the industry adopted the automatic circuit recloser as the technical solution. The device has hazardous implications for maintenance workers. The aim of this study was to analyze the origins and consequences of work accidents in power systems with automatic circuit recloser, using the Accident Analysis and Prevention (AAP) model. The AAP model was used to investigate two work accidents, aimed to explore the events' organizational origins. Case 1 - when changing a deenergized secondary line, a worker received a shock from the energized primary cable (13.8kV). The system reclosed three times, causing severe injury to the worker (amputation of a lower limb). Case 2 - a fatal work accident occurred during installation of a new crosshead on a partially insulated energized line. The tip of a metal cross arm section strap touched the energized secondary line and electrocuted the maintenance operator. The circuit breaker component of the automatic circuit recloser failed. The analyses revealed how business management logic can participate in the root causes of work accidents through failures in maintenance management, outsourced workforce management, and especially safety management in systems with reclosers. Decisions to adopt automation to guarantee power distribution should not overlook the risks to workers in overhead power lines or fail to acknowledge the importance of ensuring safe conditions.